Analisis Minat Belajar Bahasa Arab Mahasiswa Institut Agama Islam Al-Zaytun Indonesia - Nisa, Chaerul; Tanjung, Henri Peranginangin; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
In Indonesia, although the majority of the population is Muslim, many are still less interested in learning Arabic. Their obstacle and difficulty is in understanding the contents of Arabic texts. What we need to pay attention to is their interest in learning. Interest in learning plays an important role in motivating academic achievement and student success. This study aims to determine and analyze the interest in learning Arabic among IAI AL-AZIS students, identify factors that influence their interest, and investigate strategies to increase their motivation. This study uses qualitative research with a descriptive approach. Using descriptive qualitative methods, data were collected through questionnaires, interviews, and observations. And the sample consisted of 40 students, two Arabic language lecturers, and campus facility staff, by sampling using the technique homogeneous sampling. The results showed that students' interest in learning varied, with most showing a moderate level of interest. External factors, such as learning methods, internal motivation, and learning facilities, were more dominant than internal factors. Strategies to increase interest include interactive teaching methods, improving the quality of facilities, and motivational support.